Prevalent Workplace Sexual Abuse of Ready-Made Garments Female Workers in Bangladesh: Understanding the Pseudo Dynamics of This Offence from Socio-Criminological Perspective - Nath, Nikhil Chandra; Tomisra, Noor A Jannat (South Asian Journal of Social Sciences and Humanities, 2024)
Safe workplace for women is a matter of great concern, even with the increasing rate of their participation in the economic sphere of Bangladesh. In spite of extensive empirical research focusing on infectious crime as sexual harassment across various spheres of human existence, even in the twentieth and twenty-first centuries, sexual harassment remains a painstaking global thorn in the flesh. Though the prevalence of sexual harassment is at its peak, a significant proportion of society normalizes this as a custom and manifests it by keeping silent about sexual harassment against RMG female workers. The primary objective of this study is to understand the victims' experiences and the major factors behind the sexual harassment at ready-made garment factories in Bangladesh. This study utilizes qualitative research methodology employing purposive snowball sampling of 20 working women and 5 KII in-depth interviews, aiming to delve into the underlying factors of this behavior from a socio-criminological perspectives.
Keywords: Sexual Harassment; RMG; Female workers; workplace; Bangladesh